Anatomical Examinations of Selected Wood Species of Nigerian Genera in Anacardiaceae Family - Adeniyi Ifedayo Michael; Alao Oluwaseyi John; Areo Olusola Samuel; Olayiwola Yetunde Bolarinwa (Mediterranean Journal of Social Sciences, 2022)
Nigerian Anacarddiacea family was investigated in this study on the account of their inherent structures with a view to bringing to the fore those features that could facilitate identification towards proper utilization based on wood quality. Mature wood species of Lannea grandis, Lannea welwitchii, Mangifera indica, Nothospondis staudtia, Pseudospondias microcarpa, Sclerocarya burrea, Sorindeia trimeris, Spondias mangifera, Spondias mombin and Trichoscypha acuminate were got from the Forestry Research Institute of Nigeria herbaratum, in Ibadan. Wood samples from the wood species were sectioned into cross sectional, tangential and radial sections of about 20μm thick using a Reichert sliding microtome. Photomicrographs were taken using a digital camera mounted on a Reichert light microscope at 40 ×. The results showed that vessels were large in all the wood species except in Lannea species, Sclerocarya burrea, Nothospondis staudtia and Trichoscypha acuminata. Body ray cells were procumbent with one row of upright and/or square marginal cells in all the wood species, but could be up to four rows in Sorindeia trimeris. Generally, septate fibres, silica,crystals and gum were observed in almost all the wood species, yet, fibre pits in Mangifera indica, Nothospondis staudtia, Pseudospondias microcarpa, Sclerocarya burrea, Spondias mombin, and L. grandis were not as bordered as they were in L. acida, L. welwitchii, Sorindeia trimeris, Spondias mangifera, and Trichoscypha acuminata. S..mombin and S. mangifera can be separated on this account. It also appears that rays were storied only in Sorindeia trimeris and L. grandis. In the aspect of wood utilization, some were expected to possess fine texture, lustrous patterns and also regions of failures as a result of high rays. Received: 11 April 2022 / Accepted: 30 June 2022 / Published: 5 July 2022